Implementasi dan Evaluasi Website Profil Desa untuk Optimalisasi Promosi Potensi Wisata dan UMKM: Studi Kasus Desa Ketindan - Zikrie Pramudia Alfarhisi; Salnan Ratih Asriningtias; Novita Rosyida; Dwi Utari Surya (Kontibusi: Jurnal Kontribusi Kepada Masyarakat, 2026)
The rapid development of information technology has encouraged the use of the internet as an effective source of information and promotional media. Ketindan Village in Lawang District, Malang Regency, has tourism potential and local Micro, Small, and Medium Enterprises (MSMEs) that have not been optimally promoted. This community service program aims to implement a village profile website as a platform for public information and local promotion. The methods include preliminary study, problem identification, data collection, needs analysis, website development, testing, installation, and training. The results show that the developed website enhances information accessibility, expands MSME and tourism promotion reach, and encourages community participation in digital publication. The effectiveness of publication increased monthly visitor, supported by an increase in published product information. The operator training improves the capacity to update website content. Therefore, implementing a village profile website supports digital village development strategies and expands the reach of village promotion.